Site‐Selective C−S Bond Formation at C−Br over C−OTf and C−Cl Enabled by an Air‐Stable, Easily Recoverable, and Recyclable Palladium(I) Catalyst. Issue 38 (20th August 2018) - Scattolin, Thomas; Senol, Erdem; Yin, Guoyin; Guo, Qianqian; Schoenebeck, Franziska
Abstract: This report widens the repertoire of emerging Pd I catalysis to carbon–heteroatom, that is, C−S bond formation. While Pd 0 ‐catalyzed protocols may suffer from the formation of poisonous sulfide‐bound off‐cycle intermediates and lack of selectivity, the mechanistically diverse Pd I catalysis concept circumvents these challenges and allows for C−S bond formation (S–aryl and S–alkyl) of a wide range of aryl halides. Site‐selective thiolations of C−Br sites in the presence of C−Cl and C−OTf were achieved in a general and a priori predictable fashion. Computational, spectroscopic, X‐ray, and reactivity data support dinuclear Pd I catalysis to be operative. Contrary to air‐sensitive Pd 0, the active Pd I species was easily recovered in the open atmosphere and subjected to multiple rounds of recycling. Abstract : Whereas palladium(0)‐catalyzed processes may suffer from the formation of poisonous sulfide‐bound off‐cycle intermediates and lack of selectivity, the mechanistically diverse Pd I catalysis concept circumvents these challenges and allows for C−S bond formation for a wide range of aryl halides. Site‐selective thiolations of C−Br sites in the presence of C−Cl and C−OTf were achieved in a general and predictable fashion.